Family Wellbeing and Neglect Patterns in Blends on Adolescents: A Case of Mukono Town Council - Brendah Karigirwa (Uganda Christian University, 2024)
The study sought to examine the effect of family wellbeing on neglect patterns in blends among adolescents: a case of Mukono Town Council. The study was guided by three objectives: establishing the relationship between economic wellbeing of the family and neglect patterns among adolescents, determining the relationship between social wellbeing of the family and neglect patterns among adolescents, and investigating the relationship between emotional wellbeing of the family and neglect patterns among adolescents in Mukono Town Council. The study was carried out using cross-sectional research design where quantitative research approach and qualitative research approach was utilized. Questionnaires were used to collect data from the teenagers/ adolescents aged 12-18 years from selected heads of blended families in Mukono Town Council, whereas interviews were conducted with key informants who are the Probation Officer, LC1 chairman, local councillors & social workers The study found strong positive relationships between family well-being dimensions and neglect patterns among adolescents in blended families in Mukono Town Council, with economic well-being (less than 5%), social well-being (less than 5%), and emotional well-being (less than 5%) all significantly associated with lower levels of neglect. Families with better economic stability, positive social interactions, and emotional support were less likely to experience neglect, highlighting the importance of economic, social, and emotional support in reducing neglect and fostering a supportive environment for adolescents in blended families. The study suggested targeted economic support programs for example Financial assistance for low income families , access to quality health care. Strengthened social support networks through implementing initiatives like community centers that offer various services for example counseling, support groups and skill building work shops. Enhanced emotional support in families, through creating space for open discussions and expression of feelings and engaging in activities that promote emotional wellbeing for example sharing experiences, practicing active listening and offering empathy. Enhanced educational programs to increase awareness about neglect and improve on family well-being in blended families in Mukono Town Council.